2015
DOI: 10.1134/s1021443715040056
|View full text |Cite
|
Sign up to set email alerts
|

The physiological and biochemical responses of eastern purple coneflower to freezing stress

Abstract: The freezing hardiness (expressed as LT 50 ) as well as changes in the antioxidant enzymes activity, total protein and lipid peroxidation (MDA content), total phenolic and flavonoid content, antioxidant capacity, chlorophyll fluorescence (F v /F m ) of Echinacea purpurea (L.) Moench were investigated. Five month old purple coneflower seedlings were kept at 4°C for two weeks to induce cold acclimation. The acclimated seedlings were treated with freezing temperatures (0, -4, -8, -12, -16, and -20°C) for 6 h. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In this study, the contents of PRO, SS and SP in shoots of LR nectarine cultivars were found to be lower than MR and HR cultivars at all timepoints during overwintering, suggesting that the high contents of these three osmoregulatory substances contributed positively to the cold resistance of nectarine. In addition to them, MDA can also be used as an important index for the cold resistance evaluation of plants [17] and its content was generally negatively correlated with cold resistance [43]. Consistently, our study found that the MDA contents of HR cultivars were lower than MR and LR cultivars.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the contents of PRO, SS and SP in shoots of LR nectarine cultivars were found to be lower than MR and HR cultivars at all timepoints during overwintering, suggesting that the high contents of these three osmoregulatory substances contributed positively to the cold resistance of nectarine. In addition to them, MDA can also be used as an important index for the cold resistance evaluation of plants [17] and its content was generally negatively correlated with cold resistance [43]. Consistently, our study found that the MDA contents of HR cultivars were lower than MR and LR cultivars.…”
Section: Discussionsupporting
confidence: 85%
“…Low-temperature stress can induce an increase in ROS content in plants, and with the deepening of stress, the accumulation of ROS exceeds the range that plants can tolerate, leading to adverse effects [ 60 ]. In this study, CAT activity increased rapidly at −10 °C and then decreased slowly; the trend of CAT activity change was the same as that of Echinacea under LT induction [ 61 ], and both peaked at LT stress. SOD decreased after rising at −10 °C, and then rose rapidly to reach a peak at −25 °C, while POD gradually increased with the decrease in temperature.…”
Section: Discussionmentioning
confidence: 62%
“…The reduction of POD activity might be due to the inhibition of enzyme synthesis or change in the assembly of enzyme subunits under stress conditions (Abedi, Pakniyat, 2010). Decreased enzyme activity has been reported under low temperature (Asadi-Sanam et al, 2015), insecticide stress (Bashir et al, 2007) and drought (Abedi, Pakniyat, 2010). The higher activity of POD, SOD and APX under freezing conditions is a sound indication of Thymus species ability to cope with ROS.…”
mentioning
confidence: 99%